Effect of Issatchenkia terricola WJL-G4 on Deacidification Characteristics and Antioxidant Activities of Red Raspberry Wine Processing - Hongying He; Yuchen Yan; Dan Dong; Yihong Bao; Ting Luo; Qihe Chen; Jinling Wang (Journal of Fungi, 2021)
Our previous study isolated a novel Issatchenkia terricola WJL-G4, which exhibited a potent capability of reducing citric acid. In the current study, I. terricola WJL-G4 was applied to decrease the content of citric acid in red raspberry juice, followed by the red raspberry wine preparation by Saccharomyces cerevisiae fermentation, aiming to investigate the influence of I. terricola WJL-G4 on the physicochemical properties, organic acids, phenolic compounds and antioxidant activities during red raspberry wine processing. The results showed that after being treated with I. terricola WJL-G4, the citric acid contents in red raspberry juice decreased from 19.14 ± 0.09 to 6.62 ± 0.14 g/L, which was further declined to 5.59 ± 0.22 g/L after S. cerevisiae fermentation. Parameters related to CIELab color space, including L*, a*, b*, h°, and ∆E* exhibited the highest levels in samples after I. terricola WJL-G4 fermentation. Compared to the red raspberry wine pretreated without deacidification (RJO-SC), wine pretreated by I. terricola WJL-G4 (RJIT-SC) exhibited significantly decreased contents of gallic acid, cryptochlorogenic acid, and arbutin, while significantly increased contents of caffeic acid, sinapic acid, raspberry ketone, quercitrin, quercetin, baicalein, and rutin. Furthermore, the antioxidant activities including DPPH· and ABTS+· radical scavenging were enhanced in RJIT-SC group as compared to RJO-SC. This work revealed that I. terricola WJL-G4 had a great potential in red raspberry wine fermentation.